A Morphometric Study to Measure the Height and Width of Pedicles of Second Cervical Vertebrae in Different Sex - Banu, Masuma Akhtar; Ara, Shamim; Yusuf, Rehena (Bangladesh Journal of Anatomy, 2015)
Context: Identification provides a biological profile of an individual, including estimation of ancestry, age and particularly sex by the morphology of bones. Examination of bone is important for identification and estimation of sex of an individual. The present study was planned to collect data regarding morphometric measurements of pedicle of human dry ossified second cervical vertebrae and to find out possible variations in different sex. Materials and Methods: A cross-sectional analytical study was performed in the Department of Anatomy, Dhaka Medical College, Dhaka from January 2012 to December 2012. The study materials consists of 156 (one hundred & fifty six) human dry ossified second cervical vertebral of unknown sex. The study samples were distributed in male & female sex groups by discriminant function analysis technique. With the help of digital slide calipers different measurements were recorded in millimeters. Result: Among 156 vertebrae 87 was male and 69 was female. The mean (±SD) The mean (± SD) height and width of pedicle was greater in male than that of female (P<0.05). Conclusion: There was no significant difference in height and width of pedicle, between right and left side in both sexes. Bangladesh Journal of Anatomy July 2015, Vol. 13, No. 2, pp. 37-40